Linking Empowering Leadership and Employee Creativity: The Influence of Psychological Empowerment, Intrinsic Motivation, and Creative Process Engagement - Zhang, Xiaomeng; Bartol, Kathryn M. (Academy of Management Journal, 2010)
Synthesizing theories of leadership, empowerment, and creativity, this research built and tested a theoretical model linking empowering leadership with creativity via several intervening variables. Using survey data from professional employees and their supervisors in a large information technology company in China, we found that, as anticipated, empowering leadership positively affected psychological empowerment, which in turn influenced both intrinsic motivation and creative process engagement. These latter two variables then had a positive influence on creativity. Empowerment role identity moderated the link between empowering leadership and psychological empowerment, whereas leader encouragement of creativity moderated the connection between psychological empowerment and creative process engagement.